2012
DOI: 10.1111/j.1365-3156.2012.02964.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of an ELISA test for the serological diagnosis of human fascioliasis in different epidemiological situations

Abstract: Objectives  To improve the diagnosis of human fascioliasis caused by Fasciola hepatica and Fasciola gigantica, we evaluated the diagnostic accuracy of an enzyme‐linked immunosorbent assay (ELISA), with Fasciola antigen from the adult liver fluke, for the detection of IgG against fascioliasis in human sera. Methods  The sera of 54 fascioliasis cases, originating from three endemic areas, were used in this evaluation: (i) a hyperendemic F. hepatica area where humans usually shed a great number of parasite eggs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…can elicit a specific antibody response which can be detected by Ab-ELISA as early as 1 to 2 weeks after infection (44), while shedding eggs are found in feces 10 to 12 weeks postinfection (30). Antibody detection tests are useful for determining seroprevalence in epidemiological studies but are not necessarily good indicators of active infection (44). A review (11) suggested that the most accurate, sensitive, and specific information could be determined easily and with low costs, making DNA-based tools available to investigate the epidemiology of the liver fluke in a laboratory with limited financial resources (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…can elicit a specific antibody response which can be detected by Ab-ELISA as early as 1 to 2 weeks after infection (44), while shedding eggs are found in feces 10 to 12 weeks postinfection (30). Antibody detection tests are useful for determining seroprevalence in epidemiological studies but are not necessarily good indicators of active infection (44). A review (11) suggested that the most accurate, sensitive, and specific information could be determined easily and with low costs, making DNA-based tools available to investigate the epidemiology of the liver fluke in a laboratory with limited financial resources (11).…”
Section: Discussionmentioning
confidence: 99%
“…Fasciola spp. can elicit a specific antibody response which can be detected by Ab-ELISA as early as 1 to 2 weeks after infection (44), while shedding eggs are found in feces 10 to 12 weeks postinfection (30). Antibody detection tests are useful for determining seroprevalence in epidemiological studies but are not necessarily good indicators of active infection (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FhFtn-1 and FhTP16.5 ELISAs were compared with an ELISA (DRG test; DRG Instruments GmbH, Germany) that is based on excretory-secretory products (ESPs) from adult F. hepatica, mainly containing cysteine proteases (27,28). This test was used with a subset of 86 serum samples selected among those that had been used previously to validate the FhFtn-1 and FhTP16.5 ELISAs.…”
Section: Methodsmentioning
confidence: 99%
“…One of these assays (Ildana Biotech) uses recombinant forms of cathepsin L1 as antigens and has been optimized for detection of antibodies in the serum and milk of cattle (26). Others methods, as the AccuDiag Fasciola IgG ELISA (Diagnostic Automation/Cortez Diagnostic, Inc.), Bio-X, and DRG (DRG Instruments GmbH, Germany) kits, have been optimized for detection of antibodies in the sera of cattle (27) and humans (28). These assays use ESPs as antigens, which could limit their usefulness due to cross-reactions with other parasites (27,28).…”
mentioning
confidence: 99%